Idiopathic Mesenteric Phlebosclerosis: A Single-Institute Experience in Taiwan - Chou, Jen-Wei; Chang, Chia-Hsi; Wu, Yi-Hua; Chang, Kai-Chih; Cheng, Ken-Sheng; Huang, Po-Ju (Turkish Journal of Gastroenterology, 2023)
Background: Idiopathic mesenteric phlebosclerosis is a rare condition with unclear pathogenesis. This study aimed to investigate the clinical features, diagnostic modalities, treatments, and outcomes of idiopathic mesenteric phlebosclerosis patients in Taiwan. Methods: Idiopathic mesenteric phlebosclerosis patients diagnosed by the typical characteristic of tree-like mesenteric venous calcifications on plain abdominal radiography or computed tomography between January 1992 and July 2021 were retrospectively analyzed. Results: Totally, 36 idiopathic mesenteric phlebosclerosis patients were enrolled (50% females; mean age, 61.6 years). Among the included patients, 26 (72.2%) and 10 (27.7%) were symptomatic and asymptomatic, respectively. Abdominal pain (61.1%) accounted for the majority of all symptoms, followed by fever, diarrhea, and bloody stools. Our results showed that 83.3% of patients had at least 1 risk factor, whereas 16.6% of patients had none. Moreover, among the included patients, 36.1%, 44.4%, 50.0%, 38.8%, and 8.3% had cardiovascular disease, chronic renal disease, cancer, chronic liver disease, and diabetes mellitus, respectively. Our findings showed 94.4% of patients were diagnosed via abdominal computed tomography and plain abdominal radiography, whereas 5.6% of patients were diagnosed via plain abdominal radiography. The ascending colon was the most commonly involved site (100%). Our findings showed that 91.6% of patients experienced good recovery after conservative treatment, except for the 3 who died of sepsis and respiratory failure. By contrast, 8.3% of idiopathic mesenteric phlebosclerosis patients underwent colectomy. The average follow-up duration was 62.5 months. Conclusions: Idiopathic mesenteric phlebosclerosis remains a rare disease in Taiwan. Plain abdominal radiography and computed tomography can be utilized for establishing a definite diagnosis. Conservative treatment is usually adequate for most patients, with surgical treatment only indicated for severe cases. Cite this article as: Chou J, Chang C, Wu Y, Chang K, Cheng K, Huang P. Idiopathic mesenteric phlebosclerosis: A single-institute experience in taiwan. Turk J Gastroenterol. 2023;34(5):483-489.